2021
DOI: 10.3390/antiox10111735
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Melatonin on Saccharomyces cerevisiae under Ethanol Stress

Abstract: During alcoholic fermentation, Saccharomyces cerevisiae is subjected to several stresses, among which ethanol is of capital importance. Melatonin, a bioactive molecule synthesized by yeast during alcoholic fermentation, has an antioxidant role and is proposed to contribute to counteracting fermentation-associated stresses. The aim of this study was to unravel the protective effect of melatonin on yeast cells subjected to ethanol stress. For that purpose, the effect of ethanol concentrations (6 to 12%) on a win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…However, the YPD medium used in this study contained only 20 g L –1 glucose, which was insufficient to produce high osmotic stress. Furthermore, the ethanol concentration in the fermentation product (∼0.78%) was far below the commonly used 6% ethanol content for ethanol stress experiments and also below the upper limit of 13% ethanol concentration in fermentation solutions specified by ethanol production plants . In this experiment, yeast was completely exposed to a high oxygen environment during the initial phase of fermentation, suggesting that ROS in the fermentation solution may primarily originate from the mitochondrial respiratory chain .…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…However, the YPD medium used in this study contained only 20 g L –1 glucose, which was insufficient to produce high osmotic stress. Furthermore, the ethanol concentration in the fermentation product (∼0.78%) was far below the commonly used 6% ethanol content for ethanol stress experiments and also below the upper limit of 13% ethanol concentration in fermentation solutions specified by ethanol production plants . In this experiment, yeast was completely exposed to a high oxygen environment during the initial phase of fermentation, suggesting that ROS in the fermentation solution may primarily originate from the mitochondrial respiratory chain .…”
Section: Resultsmentioning
confidence: 78%
“…Notably, among the four nanozymes, FeN 3 P-SAzyme exhibited the highest SODlike activity. Prior research has indicated that SOD was activated before CAT in yeast cells under stress conditions, 11 as CAT was responsible for detoxifying H 2 O 2 generated from the conversion of •O 2 − by SOD. 59 Consequently, the presence of nanozymes in the fermentation environment facilitated the early elimination of •O 2 − by cells, with the resulting H 2 O 2 promoting the activation of endogenous CAT in cells.…”
Section: Pod-like Cat-like and Sod-like Activities Of Nanozymes Hydro...mentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of MDA, the activities of SOD, and the GSH level were determined using commercial kits (Nanjing Jiancheng., Nanjing, China). MDA was determined based on the spectrophotometer measurement of the red complex produced during the reaction of thiobarbituric acid (TBA) with the MDA [ 18 ]. The cellular MDA was expressed as nmol/mg of cellular protein.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the strains with the highest melatonin production belong to S. cerevisiae, among which those isolated from wine-related environments stand out. Melatonin synthesis in yeast have been associated with an antioxidant role [29][30][31] and a protective molecule against ethanol stress [32]. Wine fermentation is a very stressful process which can promote the adaptation to this harsh environment by promoting the synthesis of these protective molecules against the multiple stresses.…”
Section: Biosensor Evaluationmentioning
confidence: 99%